Effects of carvedilol on structural and functional outcomes and plasma biomarkers in the mouse transverse aortic constriction heart failure model. (22nd March 2017) - Hampton, Caryn; Rosa, Raymond; Szeto, Daphne; Forrest, Gail; Campbell, Barry; Kennan, Richard; Wang, Shubing; Huang, Chin-Hu; Gichuru, Loise; Ping, Xiaoli; Shen, Xiaolan; Small, Kersten; et al.
Introduction: Despite the widespread use of the mouse transverse aortic constriction heart failure model, there are no reports on the characterization of the standard-of-care agent carvedilol in this model. Methods: Left ventricular pressure overload was produced in mice by transverse aortic constriction between the innominate and left common carotid arteries. Carvedilol was administered at multiple dose levels (3, 10 and 30 mg/kg/day per os ; yielding end-study mean plasma concentrations of 0.002, 0.015 and 0.044 µM, respectively) in a therapeutic design protocol with treatment initiated after the manifestation of left ventricular remodeling at 3 weeks post transverse aortic constriction and continued for 10 weeks. Results: Carvedilol treatment in transverse aortic constriction mice significantly decreased heart rate and left ventricular dP/dt (max) at all dose levels consistent with β-adrenoceptor blockade. The middle dose of carvedilol significantly decreased left ventricular weight, whereas the higher dose decreased total heart, left and right ventricular weight and wet lung weight compared to untreated transverse aortic constriction mice. The higher dose of carvedilol significantly increased cardiac performance as measured by ejection fraction and fractional shortening and decreased left ventricular end systolic volume consistent with the beneficial effect on cardiac function. End-study plasma sST-2 and Gal-3 levels did not differ among sham, transverse aortic constriction control and transverse aortic constriction carvedilol groups. Plasma b rain natriuretic peptide concentrations were elevated significantly in transverse aortic constriction control animals (~150%) compared to shams in association with changes in ejection fraction and heart weight and tended to decrease (~30%, p = 0.10–0.12) with the mid- and high-dose carvedilol treatment. Conclusion: A comparison of carvedilol hemodynamic and structural effects in the mouse transverse aortic constriction model versus clinical use indicates a strong agreement in effect profiles preclinical versus clinical, providing important translational validation for this widely used animal model. The present plasma brain natriuretic peptide biomarker findings support the measurement of plasma natriuretic peptides in the mouse transverse aortic constriction model to extend the translational utility of the model.